An Exogenous Surfactant-Producing Bacillus subtilis Facilitates Indigenous Microbial Enhanced Oil Recovery - Gao, Peike; Li, Guoqiang; Li, Yanshu; Li, Yan; Tian, Huimei; Wang, Yansen; Zhou, Jiefang; Ma, Ting (Frontiers in Microbiology, 2016)
This study used an exogenous lipopeptide-producing Bacillus subtilis to strengthen the indigenous microbial enhanced oil recovery (IMEOR) process in a water-flooded reservoir in the laboratory. The microbial processes and driving mechanisms were investigated in terms of the changes in oil properties and the interplay between the exogenous Bacillus subtilis and indigenous microbial populations. The exogenous Bacillus subtilis is a lipopeptide producer, with a short growth cycle and no oil-degrading ability. The Bacillus subtilis facilitates the IMEOR process through improving oil emulsification and accelerating microbial growth with oil as the carbon source. Microbial community studies using quantitative PCR and high-throughput sequencing revealed that the exogenous Bacillus subtilis could live together with reservoir microbial populations, and did not exert an observable inhibitory effect on the indigenous microbial populations during nutrient stimulation. Core-flooding tests showed that the combined exogenous and indigenous microbial flooding increased oil displacement efficiency by 16.71%, compared with 7.59% in the control where only nutrients were added, demonstrating the application potential in enhanced oil recovery in water-flooded reservoirs, in particular, for reservoirs where IMEOR treatment cannot effectively improve oil recovery.